Spectres of false divinity Hume's moral atheism - Holden, Thomas Anand (Oxford : Oxford University Press, 2010)
Thomas Holden presents a historical & critical interpretation of Hume's rejection of the existence of a deity with moral attributes. Hume's 'moral atheism' is a central plank both of his naturalistic agenda in metaphysics & his secularizing program in moral theory.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Hume, David, -- 1711-1776 -- Ethics; Religion and ethics; Atheism